Preparation method of artificial joint surface titanium-carbon nano multilayer composite wear-resistant coating material

By preparing titanium carbon nano-multi-layer composite wear-resistant coating materials on the surface of artificial joints of titanium alloy, the problem of excessive wear of the friction interface of artificial joints of titanium alloy is solved by using alternating gradient arc ion plating technology and amorphous carbon lubricating layer, the problem of excessive wear and tear of titanium alloy is achieved, and higher hardness, wear resistance and service life are achieved.

CN119530724AActive Publication Date: 2025-02-28CHONGQING BIOINTELLIGENT MFG RES INST
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411823012.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-12-12
Filing Date
2024-12-11
Publication Date
2025-02-28
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

In the prior art, the titanium alloy artificial joint friction interface has problems with excessive wear, which affects the long-term and safe use of implanted prosthesis.

Method used

Titanium carbon nano-multi-layer composite wear-resistant coating material is used to prepare the Ti-TiN layer with interfacial fusion characteristics as an energy absorption layer through alternating gradient arc ion plating technology, and an amorphous carbon lubricating layer is deposited thereon.

Benefits of technology

It significantly improves the hardness and wear resistance of the coating, slows down stress cracking and fall off under impact conditions, and extends the service life of the joint prosthesis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of artificial joint preparation, and particularly relates to a preparation method of a titanium-carbon nano multilayer composite wear-resistant coating material on the surface of an artificial joint. The method comprises the steps that S01, titanium alloy for 3D printing is prepared to serve as a base material, and the base material is pretreated; s02, alternately preparing a Ti-TiN layer with an interface fusion characteristic by adopting cathode arc ion plating and anode layer ion beam; and S03, preparing the amorphous carbon lubricating layer. The titanium-carbon composite protective coating material with the multi-layer interface fusion characteristic is prepared on the basis of an alternating gradually-changing arc ion plating method by providing a composite structure thought that a bonding layer on the surface of a base body is strengthened, and a middle energy absorption layer and a top lubricating layer of an interface fusion structure are combined into a whole.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Priority application This application claims priority to the Chinese invention patent application [CN202311707996.5] "A wear-resistant coating on the surface of titanium alloy artificial joint and preparation method" filed on December 12, 2023, which is incorporated by reference in its entirety. Technical Field

[0002] The invention belongs to the technical field of artificial joint preparation, and specifically relates to a method for preparing a titanium-carbon nano multilayer composite wear-resistant coating material on the surface of an artificial joint. Background Art

[0003] The special internal environment of the human body places the most basic requirements on artificial joint materials, including: (1) excellent biocompatibility; (2) good biomechanical compatibility; (3) excellent biocompatibility and stability; (4) long service life. However, all types of artificial joints currently in use generally have problems such as easy wear, loosening, dislocation, displacement, and sharp friction noise.

[0004] 3D printed customized joints provide a new opportunity to solve the shortcomings of traditional molding methods (difficulty in molding complex modified joints, inability to produce personalized joints, etc.). Titanium alloys have good specific strength and excellent biocompatibility, which has made progress in the clinical application of personalized all-titanium joints. However, due to its poor shear strength, titanium alloys themselves face the problem of excessive wear under bio-corrosion conditions when used as joint friction interface materials, which seriously affects the long-term safe use of implanted prostheses.

[0005] The patent with publication number CN101090743A and invention name "Prosthetic joint with joint surface layer including ADLC" discloses a prosthetic joint with a surface protective coating material, the surface of which has amorphous diamond-like carbon (ADLC). The patented technology proposes to set a bonding layer between the base layer and the surface layer ADLC, including (base)-Ti-TiN-Ti-TiN. Those skilled in the art generally believe that the performance of the bonding layer is crucial to the performance of the overall coating. However, the patent does not disclose a clear and operable method for preparing the bonding layer, and the performance comparison effect in the embodiments of the patent is even more unclear. Therefore, the patent only proposes a structural design of a prosthetic joint. The research on the design and performance comparison of surface protective coating materials is not in-depth enough, and no effective surface modification technology solution has been proposed.

[0006] At present, there are usually two ways to strengthen the friction interface of 3D printed titanium alloy artificial joints: 1) Print a set of friction parts made of cobalt-chromium-molybdenum alloy separately and assemble them into the main body of the prosthesis. This method uses cobalt-chromium-molybdenum, a traditional implant material, to improve the biological and tribological properties of the friction interface and extend the service life of the joint. However, this method has the disadvantages of long production and design cycle and high cost of joint prosthesis. More importantly, the method of block printing-assembly-in-one use will also lead to multiple interfaces of dissimilar metal contact in the prosthesis. The existence of these interfaces will cause problems such as interfacial galvanic corrosion and micro-friction during the use of the joint prosthesis. Not only can the advantages of 3D printing in the design and processing of personalized joint prostheses not be fully utilized, but it may even bring other potential hazards. 2) Prepare high-strength and wear-resistant coating materials on the surface of titanium alloy to improve the service life of joint prostheses. This method uses surface engineering technology to prepare a protective coating material with wear resistance and high hardness on the surface of the prosthesis. It is usually prepared by modified physical vapor deposition method, but this method usually has high requirements for the selection of material system and the accuracy of preparation process. It is necessary to accurately control the composition-structure of the coating to achieve the preparation of high-performance coating.

[0007] In summary, it is necessary to propose new specific feasible methods and strategies to alleviate the shortcomings of existing technologies. Summary of the invention

[0008] The purpose of the present invention is to provide a titanium-carbon nano multilayer composite wear-resistant coating material on the surface of an artificial joint and its preparation method and application, so as to partially solve or alleviate the above-mentioned deficiencies in the prior art. The present invention specifically adopts the following technical solutions.

[0009] One aspect of the present invention provides a preparation method.

[0010] A method for preparing a titanium-carbon nano-multilayer composite wear-resistant coating material comprises the following steps: S010: Prepare a titanium alloy for 3D printing as a base material, place the base material on a sample holder of the equipment, and rotate the sample holder to the front of the linear ion beam of the anode layer, introduce argon (Ar) into the linear ion beam of the anode layer and ionize it, and pre-treat (etch) the base material to remove the surface oxide film; S020: using cathode arc ion plating and anode layer ion beam alternately to prepare a Ti-TiN layer having an interface fusion characteristic, and setting the thickness of the prepared Ti-TiN layer to be 1.5-3.0 μm; S021: setting a constant current, setting an argon gas flow rate to f1, and depositing on the substrate material for a time of t1 to prepare a Ti layer; S022: setting a constant current, setting a nitrogen flow rate to f2, and depositing on the Ti layer for t2 to prepare a TiN layer; then reducing the nitrogen flow rate to f3 / min, and introducing argon at a rate of f4 / min, and gradually changing the two gases to make the TiN layer transition to the Ti layer, and the duration is t3; S023: set a constant current, set the argon flow rate to f1, set the deposition time to t4, and prepare a Ti layer; reduce the argon flow rate at a rate of f4 / min, and increase the nitrogen flow rate at a rate of f3 / min, and gradually change the two gases to make the Ti layer transition to the TiN layer (until the TiN layer is prepared), and the duration is t5; Wherein, the argon gas flow rate f1 is less than the nitrogen gas flow rate f2; the gas flow rate f3 / min is greater than the gas flow rate f4 / min; Wherein, the argon flow rate f1 is 150-200 sccm; the deposition time t1 is 10-30 minutes; the nitrogen flow rate f2 is 400-450 sccm; the deposition time t2 is 5-20 minutes; the gas flow rate f3 / min is 45-90 sccm / min; the time t3 is 5-10 minutes; the gas flow rate f4 / min is 20-40 sccm / min; the time t4 is 5-10 minutes; the time t5 is 5-10 minutes; Repeat S022-S023, so that the last layer prepared is a Ti layer; S030: Rotate the sample holder to the front of the anode layer ion beam, set a constant current, set the C2H2 gas flow rate to 40-50 sccm, and deposit for 30-40 minutes to prepare an amorphous carbon (DLC) lubricating layer.

[0011] Amorphous carbon materials have high hardness, high biosafety and excellent wear resistance, and are excellent lubricating coating materials. However, due to its high hardness, the difference between its own mechanical properties and the mechanical properties of the metal matrix is ​​too large, and it is easy to peel off and split due to mismatch of mechanical properties. Therefore, one of the focuses of the method of the present invention is to design a bonding layer material with good support and toughness for the top amorphous carbon lubricating layer. The bonding layer material has moderate hardness, plays a good supporting role between the bottom metal base layer and the top amorphous carbon layer, and can also absorb instantaneous impact energy, thereby improving the comprehensive performance of the entire composite material.

[0012] As a preferred embodiment, the deposition time in S030 is 30 minutes.

[0013] Further, the constant current set in S020 is greater than the constant currents set in S010 and S030.

[0014] Furthermore, when pre-treating the substrate material, a constant current is set, and the argon gas flow rate is set to 40-50 sccm; the equipment cavity temperature is set to be no less than 200° C., and the cavity pressure is set to be constant at 2.0 mTorr; and the deposition time is 20-30 minutes.

[0015] As a preference, the argon gas flow rate is set to 48-50 sccm; and the equipment cavity temperature is set to 200°C.

[0016] As a preferred embodiment, the deposition time in S010 is 30 minutes.

[0017] Furthermore, in S021, the temperature of the equipment cavity is set to be no less than 200° C., the cavity pressure is set to be 40-50 mTorr; the argon gas flow rate f1 is set to be 200 sccm; and the time t1 is set to be 10-20 minutes.

[0018] As a preference, the temperature of the equipment cavity is set to 200-230° C.; the cavity pressure is set to 45 mTorr.

[0019] Furthermore, in S022, the equipment cavity temperature is set to be no less than 200° C., the cavity pressure is set to be 40-50 mTorr; the nitrogen flow rate f2 is set to be 450 sccm; and the time t2 is set to be 5-10 minutes.

[0020] As a preference, the temperature of the equipment cavity is set to 200-230° C.; the cavity pressure is set to 45 mTorr.

[0021] Furthermore, in S022, the nitrogen introduction rate f3 / min is reduced to 45-90 sccm / min, the argon introduction rate f4 / min is set to 20-40 sccm / min, and the time t3 is 5-10 minutes.

[0022] Further, the constant current is set to 70A in S020; and the constant current is set to 0.2A in S030.

[0023] Another aspect of the present invention provides a product obtained by the above preparation method.

[0024] The titanium-carbon nano-multilayer composite wear-resistant coating material prepared by the above preparation method is composed of a base material, an intermediate energy absorption layer and a top amorphous carbon lubricating layer from bottom to top; the intermediate energy absorption layer is an alternately deposited Ti-TiN layer with interface fusion characteristics. Alternatively, the titanium-carbon nano-multilayer composite wear-resistant coating material is provided with an alternately deposited Ti-TiN layer with interface fusion characteristics as the intermediate energy absorption layer.

[0025] Preferably, the thickness of the intermediate energy absorption layer is 1.6-3.0 μm, and the number of layers is not less than 4.

[0026] Preferably, the thickness of the intermediate energy absorption layer is 1.6-3.0 μm, and the number of layers is not less than 5.

[0027] Furthermore, a Ti layer is used as a bonding layer between the base material and the intermediate energy absorption layer; a Ti layer is used as a bonding layer between the top amorphous carbon lubricating layer and the intermediate energy absorption layer. That is, the intermediate energy absorption layer has a structure of -Ti-TiN-Ti-TiN-Ti- with interface fusion characteristics.

[0028] Furthermore, the overall thickness of the titanium-carbon nano multilayer composite wear-resistant coating material is 3-3.5 μm.

[0029] The present invention can also provide the application of the preparation method and the product.

[0030] The application of the above preparation method in the preparation of artificial wear-resistant joints.

[0031] Application of the above titanium-carbon nano multilayer composite wear-resistant coating material in the preparation of artificial wear-resistant joints.

[0032] The present invention optionally provides a most preferred preparation scheme, and the following scheme should be understood as an example rather than a limitation.

[0033] A method for preparing a titanium-carbon nano-multilayer composite wear-resistant coating material comprises the following steps: S010: Prepare a titanium alloy for 3D printing as a base material, place the base material on a sample holder of the equipment, and rotate the sample holder to the front of the linear ion beam of the anode layer, introduce argon (Ar) into the linear ion beam of the anode layer and ionize it, set the constant current to 0.2A, set the argon flow rate to 48-50sccm, and pre-treat (etch) the base material to remove the surface oxide film; S020: using cathode arc ion plating and anode layer ion beam alternately to prepare a Ti-TiN layer having an interface fusion characteristic, and setting the thickness of the prepared Ti-TiN layer to be 2.5-3.0 μm; S021: setting a constant current, setting an argon gas flow rate to f1, and depositing on the substrate material for a time of t1 to prepare a Ti layer; S022: setting a constant current, setting a nitrogen flow rate to f2, and depositing on the Ti layer for t2 to prepare a TiN layer; then reducing the nitrogen flow rate to f3 / min, and introducing argon at a rate of f4 / min, and gradually changing the two gases to make the TiN layer transition to the Ti layer, and the duration is t3; S023: setting a constant current, setting the argon flow rate to f1, and the deposition time to t4 to prepare a Ti layer; reducing the argon flow rate at a rate of f4 / min, and increasing the nitrogen flow rate at a rate of f3 / min, and gradually changing the two gases to make the Ti layer transition to the TiN layer until the TiN layer is prepared, and the duration is t5; Wherein, the argon gas flow rate f1 is less than the nitrogen gas flow rate f2; the gas flow rate f3 / min is greater than the gas flow rate f4 / min; Among them, the argon gas flow rate f1 is 200 sccm; the deposition time t1 is 20 minutes; the nitrogen gas flow rate f2 is 450 sccm; the deposition time t2 is 5 minutes; the gas flow rate f3 / min is 90 sccm / min; the time t3 is 5 minutes; the gas flow rate f4 / min is 40 sccm / min; the time t4 is 10 minutes; the time t5 is 10 minutes; Repeat S022-S023, so that the last layer prepared is a Ti layer; S030: The sample holder is rotated to the front of the anode layer ion beam, a constant current is set, a C2H2 gas flow rate is set to 48-50 sccm, and deposition is performed for 30 minutes to prepare an amorphous carbon (DLC) lubricating layer.

[0034] Beneficial technical effects: It is unacceptable for the artificial joint surface protective coating material to prematurely peel off and fail during service under the friction-corrosion coupling effect in the human body, and the fundamental reason for the peeling failure is that the coating itself has too high internal stress and insufficient bonding with the substrate. Therefore, based on the above situation, the present invention proposes a composite structure idea of ​​strengthening the substrate surface bonding layer, combining the intermediate energy absorption layer of the interface fusion structure, and the top lubricating layer as one, and successfully prepares a titanium-carbon composite protective coating material with multi-layer interface fusion characteristics based on an alternating gradient arc ion plating technology. The specific technical scheme is as follows.

[0035] First, it is proposed to use arc ion plating technology with high ionization rate and high ion energy to first prepare a Ti layer that can achieve metallurgical bonding on the surface of the artificial joint prosthesis as a bonding layer to improve the bonding performance of the overall coating, and then periodically deposit a TiN-Ti layer with interface fusion characteristics on its surface as an energy absorption layer to reduce the internal stress of the overall coating, and effectively slow down the stress cracking phenomenon generated during the friction impact process, thereby avoiding the brittle fracture and peeling of the entire coating when it is impacted. The reasons for selecting the TiN-Ti layer with interface fusion characteristics are as follows: the Ti layer is relatively soft and has the same mechanical properties as the base material, while the TiN layer has extremely high hardness and belongs to a hard ceramic layer. By gradually and periodically changing the introduction of the reaction gas Ar-N2 during the deposition process, a TiN-Ti layer structure with interface fusion characteristics can be achieved. This structure does not have an obvious interlayer interface structure, but has the characteristics of a soft (Ti layer)-hard (TiN) alternating structure. It can effectively absorb and release the stress transmitted by the joint surface when the joint faces instantaneous impact (such as human jumping and running), and avoid the formation of through cracks and failure of the entire coating. Finally, a smooth and dense amorphous carbon layer is prepared on the top of the multilayer structure by using anodic ion beam deposition technology as a top lubricating layer. The present invention particularly proposes to prepare a variety of materials with interfacial fusion characteristics and alternately deposited Ti-TiN layers by changing the deposition time on the basis of setting a specific thickness range, and experimentally screen out the multilayer structure material with the best comprehensive effect.

[0036] The titanium-carbon nano multilayer composite wear-resistant coating material prepared by the present invention has improved hardness and wear resistance compared to other nitrogen-based coating wear-resistant coating materials, and also has good energy absorption characteristics, which can slow down the stress cracking and shedding phenomenon of the coating under impact conditions.

[0037] Compared with other wear-resistant coating preparation technologies, the alternating gradient arc ion plating technology proposed in the present invention has a large design range and high process controllability for the composite structure coating material. The prepared coating material can be used as the final product instead of using other additional processing (such as polishing) processes. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. In all the drawings, similar elements or parts are generally identified by similar reference numerals. In the drawings, each element or part is not necessarily drawn according to the actual scale. Obviously, the drawings described below are some embodiments of the present invention. For those of ordinary skill in the art, other drawings can also be obtained based on these drawings without paying creative labor.

[0039] Figure 1Schematic diagram of the structure of the vacuum coating equipment used in the present invention (the left side is the cathode arc target, and the Ti and TiN layers are prepared by controlling the type of gas introduced, and the right side is the anode layer ion source, and acetylene is introduced into the anode layer to prepare the top amorphous carbon layer); Figure 2 Schematic diagram of the structure of the titanium-carbon multilayer coating prepared in Example 1 of the present invention (intermediate layer Ti:TiN=5:5); Figure 3 Schematic diagram of the structure of the titanium-carbon multilayer coating prepared in Example 2 of the present invention (intermediate layer Ti:TiN=3:3); Figure 4 Schematic diagram of the structure of the titanium-carbon multilayer coating prepared in Example 3 of the present invention (intermediate layer Ti:TiN=1:1); Figure 5 Schematic diagram of the structure of a Ti-TiN multilayer coating without a top amorphous carbon layer prepared in Example 4 of the present invention (Ti:TiN=4:4); Figure 6 The cross-sectional structure morphology and energy spectrum line scanning results of the Ti / TiN / amorphous carbon multilayer coating with interface fusion characteristics prepared in Example 2 of the present invention; Figure 7 The cross-sectional structure morphology and energy scanning result of the Ti / TiN / amorphous carbon multilayer coating with interface fusion characteristics prepared in Example 3 of the present invention; Figure 8 The cross-section and surface structure morphology of the Ti / TiN multilayer coating prepared in Example 4 of the present invention; Fig. 9 The tribological curves and wear rate results of the coating samples and 3D printed titanium alloy substrates prepared in different embodiments of the present invention when they were respectively rubbed against polytetrafluoroethylene materials; Fig.10 This is a bonding strength test of the titanium-carbon multilayer coating prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0040] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0041] Herein "and / or" includes any and all combinations of one or more of the associated listed items.

[0042] Herein, "plurality" means two or more than two, ie, it includes two, three, four, five, etc.

[0043] As used in this specification, the term "about" typically means + / - 5% of the stated value, more typically + / - 4% of the stated value, more typically + / - 3% of the stated value, more typically + / - 2% of the stated value, even more typically + / - 1% of the stated value, and even more typically + / - 0.5% of the stated value.

[0044] In this specification, some embodiments may be disclosed in a format of being in a range. It should be understood that this description of "being in a range" is only for convenience and brevity, and should not be interpreted as a rigid limitation on the disclosed range. Therefore, the description of the range should be considered to have specifically disclosed all possible sub-ranges and independent numerical values ​​within this range. For example, the description of the range 1-6 should be considered to have specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as individual numbers within this range, such as 1, 2, 3, 4, 5 and 6. Regardless of the breadth of the range, the above rules apply.

[0045] The "interface fusion characteristics" mentioned in the present invention refer to that there is no obvious interface structure between the prepared TiN layer and the Ti layer, and the contrast difference between the two has a gradual characteristic.

[0046] The titanium-carbon composite layer prepared by the present invention has the following characteristics.

[0047] Good hardness: The intermediate layer Ti / TN coating has a very high hardness, usually between 2000-3000HV, which is higher than the hardness of many metal and non-metal materials. By adjusting the ratio and interface structure of the two, a combination of good hardness and toughness can be achieved.

[0048] Good wear resistance: Due to its high hardness, titanium nitride coatings have excellent wear resistance and can significantly extend the service life of the substrate.

[0049] Good corrosion resistance: Titanium nitride coatings exhibit excellent corrosion resistance in many corrosive media, helping to protect the substrate from corrosion.

[0050] Amorphous carbon coating: Amorphous carbon is a type of solid lubricating coating material with high hardness (the hardness of amorphous carbon coating prepared by PVD technology can reach up to 40GPa or more), good chemical stability (no chemical corrosion occurs in any solution) and self-lubricating properties, and has important applications in the aerospace field. In Example 4 of the present invention, the friction coefficient of the sample without a top amorphous carbon coating is about 0.4, which is significantly higher than the friction coefficient of about 0.1-0.2 of the sample with an amorphous carbon coating (Examples 1-3), proving that the amorphous carbon coating has self-lubricating properties.

[0051] Example 1 This embodiment provides a multi-layer titanium-carbon composite coating material. Figure 1 The vacuum coating equipment shown in FIG. 1 is used to prepare the coating structure of the embodiment. Figure 2 As shown, the specific preparation process is as follows.

[0052] 1. Preparation of substrate materials The 3D printed titanium alloy was used as the substrate material, and the substrate was polished before coating. The substrate material size is 17mm×17mm×3mm. Before depositing the coating, the 3D printed polished titanium alloy substrate was first ultrasonically cleaned in anhydrous ethanol and acetone for 15 minutes to remove oil and other impurities on the surface; then the residual liquid on the surface was dried with a hair dryer for later use.

[0053] 2. Matrix material pretreatment Sample clamping. Place the 3D printed titanium alloy substrate after the above pretreatment on the sample rack, and use a special clamp to fix the sample so that it is firmly fixed on the sample rack and has good electrical conduction with the sample rack. After placing the sample rack in the coating chamber of the equipment, use a mechanical pump and a molecular pump to evacuate the chamber, and control the chamber pressure to be less than 2.0×10 -5 Torr, the sample is pretreated before coating (i.e., sample etching pretreatment).

[0054] Sample etching pretreatment. After the vacuum degree of the vacuum chamber reaches the set value, open the chamber and heat it to 200°C. After the temperature reaches the set value, start the etching process. Argon is introduced into the linear ion beam of the anode layer and ionized. + Ions etch and clean the surface of the substrate material to remove the oxide film formed on the surface of the sample in the air, so as to increase the bonding strength between the subsequent coating material and the substrate material. The specific processing process is as follows: Ion beam setting current: 0.2 A; Ar gas flow rate: 48-50 sccm, the chamber pressure was kept constant at 2.0 mTorr by adjusting the gas flow, and the output power was 120 W; Substrate negative bias: -100 V; Etching time: 30 min.

[0055] 3. Preparation of intermediate energy absorption layer (coating) Ti layer (bonding layer): Set the cathode arc target current to 70A, the argon gas flow rate to 200 sccm (f1), the chamber pressure to 45 mTorr, the substrate negative bias voltage to -60 V, and the chamber temperature to 200℃-230℃. The deposition time is 20 minutes (t1).

[0056] TiN layer: Set the cathode arc target current to 70A, the nitrogen flow rate to 450 sccm (f2), control the chamber pressure to 45mTorr, the substrate negative bias voltage to -60 V, and the chamber temperature to 200℃-230℃. First, deposit a pure TiN layer for 5 minutes (t2), then reduce the nitrogen flow rate to 90 sccm / min (f3) within 5 minutes (t3), and introduce argon at a rate of 40 sccm / min (f4). The two gases are gradually changed to ensure stable discharge of the target material, and the interface fusion preparation of the TiN-Ti layer is achieved. The total duration is 10 minutes.

[0057] Ti layer: Set the cathode arc target current to 70A, the argon flow rate to 200 sccm (f1), control the chamber pressure to 45mTorr, the substrate negative bias voltage to -60 V, the chamber temperature to 200℃-230℃, and the deposition time to 10 minutes (t4). Then reduce the argon gas at a rate of 40sccm / min (f4), and gradually introduce nitrogen at a rate of 90sccm / min (f3), gradually realizing the preparation from pure Ti layer to pure TiN layer. The duration is 10 minutes (t5).

[0058] Repeat the above steps.

[0059] Top amorphous carbon layer: rotate the sample holder to the front of the anode layer ion beam by revolution, set the ion beam current to 0.2 A, C2H2 gas flow rate: 48-50 sccm, maintain the chamber pressure constant at 2.0 mTorr by adjusting the gas flow, output power 120 W, substrate negative bias: -100 V, deposition time 30 minutes.

[0060] Through the above preparation process, a composite coating structure with a Ti bonding layer, a Ti-TiN intermediate layer with a 5-period interface fusion structure, and a top amorphous carbon lubrication layer is finally achieved.

[0061] In this embodiment, a Ti bonding layer with a thickness of 0.6 μm (multiplied by 2) is prepared, the thickness of the intermediate alternating TiN-Ti layer is 1.6 μm, and the thickness of the top layer is 0.5 μm, with a total thickness of about 3.3 μm.

[0062] Example 2 This embodiment provides another example of a titanium-carbon composite coating material.

[0063] The preparation and pretreatment of the substrate material involved in the preparation process used in this embodiment are the same as those in Example 2, except that the number of intermediate layers and the deposition time are different. The structure of the prepared coating is as follows: Figure 3 shown.

[0064] The intermediate energy absorbing layer (coating) is prepared as follows: Ti layer (bonding layer): Set the cathode arc target current to 70A, the argon gas flow rate to 200 sccm (f1), the chamber pressure to 45 mTorr, the substrate negative bias voltage to -60 V, and the chamber temperature to 200℃-230℃. The deposition time is 20 minutes (t1).

[0065] TiN layer: Set the cathode arc target current to 70A, the nitrogen flow rate to 450 sccm (f2), control the chamber pressure to 45mTorr, the substrate negative bias voltage to -60 V, and the chamber temperature to 200℃-230℃. First, deposit a pure TiN layer for 10 minutes (t2), then reduce the nitrogen flow rate to 45sccm / min (f3) within 10 minutes (t3), and introduce argon at a rate of 20sccm / min (f4). The two gases are gradually changed to ensure stable discharge of the target material, and the interface fusion preparation of the TiN-Ti layer is achieved. The total duration is 20 minutes.

[0066] Ti layer: Set the cathode arc target current to 70A, the argon flow rate to 200 sccm (f1), the chamber pressure to 45mTorr, the substrate negative bias voltage to -60 V, the chamber temperature to 200℃-230℃, and the deposition time to 10 minutes (t4). Then, reduce the argon gas at a rate of 20 sccm / min (f4) within 10 minutes (t5), and gradually introduce nitrogen at a rate of 45 sccm / min (f3), gradually changing from a pure Ti layer to a pure TiN layer.

[0067] Taking Ti-TiN as one deposition cycle, a total of 3 deposition cycles were performed to obtain the following Figure 3 The structure shown has three periodic structure intermediate layers.

[0068] Top amorphous carbon layer: rotate the sample holder to the front of the anode layer ion beam by revolution, set the ion beam current to 0.2 A, C2H2 gas flow rate: 48-50 sccm, maintain the chamber pressure constant at 2.0 mTorr by adjusting the gas flow, output power 120 W, substrate negative bias: -100 V, deposition time 30 minutes.

[0069] In this embodiment, a Ti bonding layer with a thickness of 0.6 μm (multiplied by 2) is prepared, the thickness of the intermediate alternating TiN-Ti layer is 1.6 μm, and the thickness of the top layer is 0.5 μm, with a total thickness of about 3.3 μm.

[0070] Example 3 This embodiment provides another improved example of preparing titanium nitride coating materials based on embodiment 3.

[0071] The preparation and pretreatment of the substrate material involved in the preparation process used in this embodiment are the same as those in Example 3, except for the number of intermediate layers and the deposition time. The structure of the prepared coating is as follows: Figure 4 shown.

[0072] Optimize process parameters: Ti layer (bonding layer): Set the cathode arc target current to 70A, the argon gas flow rate to 200 sccm (f1), the chamber pressure to 45 mTorr, the substrate negative bias voltage to -60 V, and the chamber temperature to 200℃-230℃. The deposition time is 20 minutes (t1).

[0073] TiN layer: Set the cathode arc target current to 70A, the nitrogen flow rate to 450 sccm (f2), control the chamber pressure to 45mTorr, the substrate negative bias voltage to -60 V, the chamber temperature to 200℃-230℃, and deposit a pure TiN layer for 20 minutes (t2). Then, within 10 minutes (t3), reduce the nitrogen flow rate to 45sccm / min (f3), and introduce argon at a rate of 20sccm / min (f4). By gradually changing the two gases, the interface fusion preparation of the TiN-Ti layer is achieved while ensuring stable discharge of the target. The total duration is 30 minutes.

[0074] Ti layer: Set the cathode arc target current to 70A, the argon flow rate to 200 sccm (f1), control the chamber pressure to 45mTorr, the substrate negative bias voltage to -60 V, the chamber temperature to 200℃-230℃, and the deposition time to 10 minutes (t4). Then reduce the argon gas at a rate of 20sccm / min (f4), and gradually introduce nitrogen at a rate of 45sccm / min (f3), gradually changing from a pure Ti layer to a pure TiN layer, which lasts for 10 minutes (t5).

[0075] Top amorphous carbon layer: ion beam current 0.2 A, C2H2 gas flow: 48-50 sccm, the chamber pressure was kept constant at 2.0 mTorr by adjusting the gas flow, output power 120 W, substrate negative bias: -100 V, deposition time 30 min.

[0076] It can be understood that, with Ti-TiN as one deposition cycle, n deposition cycles can be performed to prepare the titanium nitride coating material as required.

[0077] Example 4 This embodiment provides an example of device operation with a titanium nitride coating without a top amorphous carbon layer.

[0078] Based on Example 1, this embodiment proposes another example of preparing a titanium nitride coating material without a top amorphous carbon coating. The difference lies in the number of intermediate layers and the deposition time. The structure of the prepared coating is as follows: Figure 5 shown.

[0079] Ti layer: set the cathode arc target current to 70A, the argon flow rate to 200 sccm (f1), the chamber pressure to 45mTorr, the substrate negative bias voltage to -60 V, the chamber temperature to 200℃-230℃, and the deposition time to 15 minutes (t1).

[0080] TiN layer: set the cathode arc target current to 70A, the nitrogen flow rate to 450 sccm (f2), the chamber pressure to 45mTorr, the substrate negative bias voltage to -60 V, the chamber temperature to 200℃-230℃, and the deposition time to 13 minutes (t2).

[0081] The above Ti-TiN layer is regarded as one cycle, and 4 cycles are deposited in total.

[0082] Top TiN layer: The process parameters are the same as the preparation process of the second TiN layer, and the deposition time is extended to 30 minutes to increase the thickness. Finally, a nitrogen-based composite coating material with a Ti-TiN alternating structure is formed.

[0083] Example 5 This example provides performance tests of multiple coating materials prepared above.

[0084] 1. Friction coefficient The coating materials prepared in Examples 1-4 and the 3D printed titanium alloy substrate materials used were used as control test groups to test the friction and wear performance. The test results of the coating friction coefficient and wear rate are shown in Tables 1 and Fig. 9 .

[0085] Table 1 Friction coefficient From the results in Table 1, we can see that the friction coefficient and wear rate of the samples prepared with the composite coating (Examples 1-4) are significantly lower than those of the base titanium alloy material, indicating that the coating can indeed significantly reduce the wear of the base material. Fig. 9It can be seen intuitively that after the amorphous carbon layer is prepared on the top layer, the friction coefficient of the coating is lower than that of the sample with TiN coating as the top layer. The amorphous carbon with lubricating effect prepared on the top layer of the surface can further reduce wear. Furthermore, from the trend of the friction coefficient curve, it can be seen that the friction coefficient of the titanium-carbon composite coating with the middle layer ratio Ti:TiN=5:5 is the lowest, and the curve is smooth and flat during the entire friction process, with minimal fluctuations, while the friction coefficient of the titanium-carbon composite coating with other middle layer ratios shows a gradual increase and obvious fluctuations. During these fluctuations, the middle layer of the coating cannot continue to provide a good stress absorption effect, resulting in localized instantaneous cracking of the coating, which will accelerate the failure of the coating. This shows that the multi-layer "interface fusion characteristics" structure can better absorb external stress. From the wear rate, it can be seen that the multi-layer titanium-carbon composite coating can reduce the wear rate by 2 orders of magnitude and significantly reduce the wear of the base material.

[0086] From the indicators of the tribological properties of the above coatings, it can be seen that a sample with a multi-layer titanium-carbon composite coating (middle layer ratio Ti:TiN=5:5) proposed in the present invention can significantly reduce substrate wear and inhibit coating peeling during long-term wear, thereby extending the service life of the coating.

[0087] 2. Coating structure characterization test Figure 6 The cross-sectional structure morphology and energy spectrum line scanning results of the Ti / TiN / amorphous carbon multilayer coating with interface fusion characteristics prepared in Example 1 of the present invention. As can be seen from the figure, there is no obvious interface structure between the dark part (TiN layer) and the light part (Ti layer), and the contrast difference between the two has a gradual characteristic, indicating that the interface structure has the characteristics of fusion. The total thickness of the coating is about 3.3μm, and the coating has no defects such as interlayer cracking.

[0088] Figure 7 The cross-sectional structure morphology and energy spectrum line scanning results of the Ti / TiN / amorphous carbon multilayer coating with interface fusion characteristics prepared in one of the embodiments 3 of the present invention are shown. From the SEM results of the cross-sectional coating, the figure shows that the total thickness of the coating is about 3.4μm, the coating interface surface is intact, and the element surface distribution energy spectrum results show that the composition transition characteristics between the Ti-TiN layers are obvious, and the contrast difference between the two has a gradual characteristic, indicating that the interface structure has the characteristics of fusion.

[0089] Figure 8The cross-sectional SEM result of the multilayer titanium nitride coating without the top layer amorphous carbon coating prepared in Example 4 of the present invention shows that there are a total of multilayer structures, and the total thickness of the coating is about 1.82μm, of which the thickness of the Ti layer is 280nm and the thickness of the middle TiN layer is 300nm. The interface surface of the coating is intact, and there is no cracking between the layers, but the coating surface is rough as a whole, and there are many large particle defects, which is one of the shortcomings of the coating prepared by ordinary arc ion plating technology; and the composition transition characteristics between the Ti-TiN layers are not obvious, indicating that the interface structure does not have the characteristics of fusion.

[0090] 3. Coating mechanical properties test The mechanical properties of the coating were tested using nanoindentation testing technology, and the test results are shown in Table 2. By comparison, it was found that the hardness of the coatings in Examples 1-4 exceeded 13 GPa, which was significantly higher than the 3.5 GPa of the 3D printed titanium alloy substrate material. This shows that the coating can significantly improve the hardness of the substrate titanium alloy. In addition, the hardness of the samples with a top layer of amorphous carbon coating (Examples 1-3) is higher than that of the samples without a top layer of amorphous carbon in Example 4, and the more cycles with interface fusion characteristics in the multilayer structure, although the overall hardness of the sample decreases to a certain extent, the elastic modulus increases, and the toughness of the surface coating is improved, which will help the coating avoid brittle fracture and improve the overall service life of the coating.

[0091] Table 2 Mechanical properties test results of coating and substrate materials 4. Test of coating and substrate bonding performance Fig.10 The bonding strength test of the titanium-carbon multilayer coating prepared in Example 1 of the present invention (intermediate layer Ti:TiN=5:5) shows that the bonding strength of the multilayer titanium-carbon composite coating prepared by the alternating gradient arc ion plating technology reaches 32N, which has good bonding performance; the bonding strength of general amorphous carbon coatings is about 20N.

[0092] It should be noted that, in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.

[0093] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation modes, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the present invention and the claims, all of which are within the protection of the present invention.

Claims

1. A method for preparing a titanium-carbon nano-multilayer composite wear-resistant coating material, characterized in that: The following steps are involved: S010: prepare a titanium alloy for 3D printing as a base material, place the base material on a sample holder of the equipment, rotate the sample holder to the front of the linear ion beam of the anode layer, introduce argon gas into the linear ion beam of the anode layer and ionize it, and pre-treat the base material to remove the surface oxide film; S020: using cathode arc ion plating and anode layer ion beam alternately to prepare a Ti-TiN layer having an interface fusion characteristic, and setting the thickness of the prepared Ti-TiN layer to be 1.5-3.0 μm; S021: setting a constant current, setting an argon gas flow rate to f1, and depositing on the substrate material for a time of t1 to prepare a Ti layer; S022: setting a constant current, setting a nitrogen flow rate to f2, and depositing on the Ti layer for t2 to prepare a TiN layer; then reducing the nitrogen flow rate to f3 / min, and introducing argon at a rate of f4 / min, and gradually changing the two gases to make the TiN layer transition to the Ti layer, and the duration is t3; S023: set a constant current, set the argon flow rate to f1, and the deposition time to t4 to prepare a Ti layer; reduce the argon flow rate at a rate of f4 / min, and increase the nitrogen flow rate at a rate of f3 / min, and gradually change the two gases to make the Ti layer transition to the TiN layer, and the duration is t5; Wherein, the argon gas flow rate f1 is less than the nitrogen gas flow rate f2; the gas flow rate f3 / min is greater than the gas flow rate f4 / min; Wherein, the argon flow rate f1 is 150-200 sccm; the deposition time t1 is 10-30 minutes; the nitrogen flow rate f2 is 400-450 sccm; the deposition time t2 is 5-20 minutes; the gas flow rate f3 / min is 45-90 sccm / min; the time t3 is 5-10 minutes; the gas flow rate f4 / min is 20-40 sccm / min; the time t4 is 5-10 minutes; the time t5 is 5-10 minutes; Repeat S022-S023, so that the last layer prepared is a Ti layer; S030: Rotate the sample holder to the front of the anode layer ion beam, set a constant current, set the C2H2 gas flow rate to 40-50 sccm, and deposit for 30-40 minutes to prepare an amorphous carbon lubricating layer.

2. The preparation method according to claim 1, characterized in that When pretreating the substrate material, a constant current is set, an argon gas flow rate is set to 40-50 sccm; the equipment cavity temperature is set to be no less than 200° C., and the cavity pressure is set to be constant at 2.0 mTorr; and the deposition time is 20-30 minutes.

3. The preparation method according to claim 1, characterized in that: In the S021, the temperature of the equipment cavity is set to be not less than 200° C., the cavity pressure is set to be 40-50 mTorr; the argon gas flow rate f1 is set to be 200 sccm; and the time t1 is set to be 10-20 minutes.

4. The preparation method according to claim 1, characterized in that: In the S022, the equipment cavity temperature is set to be not less than 200° C., the cavity pressure is set to be 40-50 mTorr; the nitrogen flow rate f2 is set to be 450 sccm; and the time t2 is set to be 5-10 minutes.

5. The preparation method according to claim 1, characterized in that: In the S022, the nitrogen introduction rate f3 / min is reduced to 45-90 sccm / min, the argon introduction rate f4 / min is set to 20-40 sccm / min, and the time t3 is 5-10 minutes.

6. The preparation method according to claim 1, characterized in that: The constant current is set to 70A in S020 and 0.2A in S030.

7. The titanium-carbon nano multilayer composite wear-resistant coating material prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The titanium-carbon nano multilayer composite wear-resistant coating material consists of a base material, an intermediate energy absorption layer and a top amorphous carbon lubrication layer from bottom to top; the intermediate energy absorption layer is Ti-TiN with interface fusion characteristics.

8. The titanium-carbon nano multilayer composite wear-resistant coating material according to claim 7, characterized in that: A Ti layer is used as a bonding layer between the base material and the intermediate energy absorbing layer; and a Ti layer is used as a bonding layer between the top amorphous carbon lubricating layer and the intermediate energy absorbing layer.

9. The titanium-carbon nano multilayer composite wear-resistant coating material according to claim 7, characterized in that: The overall thickness of the titanium-carbon nano multilayer composite wear-resistant coating material is 3-3.5 μm.

10. Use of the preparation method according to any one of claims 1 to 6 in the preparation of artificial wear-resistant joints, or use of the titanium-carbon nano multilayer composite wear-resistant coating material according to any one of claims 7 to 9 in the preparation of artificial wear-resistant joints.

Citation Information

Patent Citations

  • Prosthetic joint with articulating surface layers comprising ADLC

    CN101090743A

  • Small modulation period Ti / TiN superhard nanometer multilayer film prepared by multi-arc ion plating

    CN109440069A

  • Medium-high temperature oxidation resistant Ti / TiN multilayer coating and preparation method

    CN110257766A

  • Preparation method of TiN / DLC multilayer composite film applied to artificial joint surface

    CN113278919A

  • Method for producing Ti / TiN compound coating on surface of titanium alloy and compound coating

    CN113667943A